2021
DOI: 10.1177/18681026211020763
|View full text |Cite
|
Sign up to set email alerts
|

China’s Foreign Aid Political Drivers: Lessons from a Novel Dataset of Mask Diplomacy in Latin America during the COVID-19 Pandemic

Abstract: This study investigates a novel dataset comprised of a universe of 537 donations in 33 countries in Latin America and the Caribbean, between 11 February and 20 June 2020, which provides a high level of detail on China’s and Taiwan’s mask diplomacy. We describe who the main donors were, who the main recipients were, what was donated to each country, and which variables explain why some countries received more aid than others. Drawing on previous literature, the article advances understanding about the political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…The studies closest to this paper are Fuchs et al (2020) and Telias and Urdinez (2020). Both investigate exports of medical products from China and shed light on the roles of political and economic ties with foreign countries.…”
mentioning
confidence: 99%
“…The studies closest to this paper are Fuchs et al (2020) and Telias and Urdinez (2020). Both investigate exports of medical products from China and shed light on the roles of political and economic ties with foreign countries.…”
mentioning
confidence: 99%
“…The first two manuscripts (Jenkins, 2022; Pu and Myers, 2022) provide a snapshot of the scope of the BRI in Latin America and the geopolitical competition between China and the United States in the region. Then, the four manuscripts that follow delve into the effects of the trade war (Dussel Peters, 2022; Gachúz Maya, 2022), the mask diplomacy during the COVID-19 pandemic (Telias and Urdinez, 2022), and the recent trends in Chinese overseas finance in renewable energy (Gélvez Rubio and González, 2022).…”
Section: Contribution Of This Special Issue To the Understanding Of C...mentioning
confidence: 99%
“…The following manuscript by Telias and Urdinez (2022) analyses a novel dataset comprised of a universe of 537 donations in thirty-three countries in LAC, between 11 February and 20 June 2020, during the outbreak of the pandemic. The authors suggest that the outbreak of COVID-19 offered a unique opportunity to understand the political drivers of China's foreign aid.…”
Section: Contribution Of This Special Issue To the Understanding Of C...mentioning
confidence: 99%
“…The first academic studies analysing the economic effects of the pandemic in most cases used global computable general equilibrium models (Maliszewska et al, 2020;Baldwin and Tomiura, 2020;McKibbin and Fernando, 2020;Orlik et al, 2020;OECD, 2020;WTO, 2020). Some subsequent papers looked at individual countries such as Kenya (Socrates, 2020), Switzerland and Spain, in the latter two cases the Covid-19 containment measures being found to lead to sharp falls in trade (Buchel et al, 2020;De Lucio et al, 2020, andMinondo, 2021); concerning China, Che et al (2020) analysed total export flows, whilst Fuchs et al (2020) and Telias and Urdinez (2020) reported a fall in the exports of medical goods and Friedt and Zang (2020) in the supply of machinery parts; finally, Meier and Pinto (2020) found that US industries with a large exposure to intermediate goods imports from China experienced a sharp fall in both exports and imports.…”
Section: Literature Reviewmentioning
confidence: 99%